Analisis Kualitas Batubara Tipe Lignit Berdasarkan Kandungan Air, Nilai Kalori, dan Total Sulfur Di Kabupaten Paser Provinsi Kalimantan Timur: Analysis of Lignite Coal Quality Based on Moisture Content, Calorific Value, and Total Sulfur in Paser Regency, East Kalimantan Province - Husni; Sri Widodo; Anshariah; Suriyanto Bakri (Journal of Engineering Science and Technology Applications, 2026)
Coal quality is largely determined by physical and chemical parameters, including moisture content, calorific value, total sulfur content, air-dry loss, and ash fusion temperature. This study aims to determine the quality of lignite coal in Paser Regency, East Kalimantan Province, based on the parameters of air-dry loss, moisture content, total moisture, total sulfur, and calorific value. The method used was laboratory analysis of three coal samples—PL, M, and SM—with the tested parameters including air-dry loss, moisture content, total moisture, calorific value, and total sulfur. The results showed that sample PL had an air-dry loss of 11.04%, moisture content of 13.45%, total moisture of 24.97%, and a calorific value of 5,117 kcal/kg; sample M had an air-dry loss of 12.48%, moisture content of 13.62%, total moisture of 24.97%, and a calorific value of 4,909 kcal/kg; while sample SM had an air-dry loss of 19.34%, moisture content of 15.01%, total moisture of 32.31%, and a calorific value of 4,352 kcal/kg. Based on these results, the PL sample had the highest quality with a calorific value of 5,117 kcal/kg, due to its lower dry loss and moisture content compared to the M and SM samples. Physically, the PL sample also exhibited better characteristics, namely a darker color, producing less dust during the crushing process, and being less brittle. The conclusion of this study is that the quality of lignite coal in the study area is largely determined by its low moisture content and high calorific value, with the PL sample being the highest-quality sample among the three tested